Multiscenario Land Use Change Simulation and Its Impact on Ecosystem Service Function in Henan Province Based on FLUS‐InVEST Model - Jincai Zhang; Ling Li; Qingsong Li; Weiqiang Chen; Junchang Huang; Yulong Guo; Guangxing Ji (Ecology and Evolution)
ABSTRACT Studying the impact of future land use changes on regional ecosystem services (ES) is crucial for sustainable development planning in the region. However, there is a lack of research specifically targeting Henan Province under different future scenarios. Therefore, this study simulates four ES functions—water yield (WY), carbon storage (CS), habitat quality (HQ), and nutrient delivery ratio (NDR)—for the historical period in Henan Province. It also constructs a Comprehensive Ecosystem Service (CES) Index. Additionally, the study predicts the spatial and temporal distribution characteristics of various ES and CES under two different Shared Socioeconomic Pathways (SSP) scenarios for the future. The results of the study showed that: (1) The high simulation accuracy of the FLUS model indicates that the FLUS model is suitable for land use simulation in the study area. (2) Under the SSP2‐4.5 scenario, the area of construction land expansion is the largest, and the HQ, CS, water production capacity, and water purification capacity of Henan Province all decrease. Under the SSP5‐8.5 scenario, the area of cultivated land increased the most, and all three decreased except for the water production capacity, which increased. (3) Under the SSP2‐4.5 scenario, the area of CES decline is the largest, and the severe decline in CES mainly occurs in areas where forest land is encroached upon by urban land, followed by areas encroached upon by rural settlements, and the encroachment of arable land by construction land leads to a mild decline in CES, which accounts for the largest proportion of the area. Under the SSP5‐8.5 scenario, Henan Province has the largest area of CES rise, and most of it is dominated by mild rise, but the mean CES in 2050 is still lower compared to 2020. The results of the study can provide a reference basis for the formulation of sustainable development policies in Henan Province and provide new ideas for the study of the impacts of land use change on ES under different scenarios in the future.